Effective Regulation of Gut Microbiota With Probiotics and Prebiotics May Prevent or Alleviate COVID-19 Through the Gut-Lung Axis - Xu, Lei; Yang, Chung S.; Liu, Yanan; Zhang, Xin (Frontiers in Pharmacology, 2022)
Coronavirus disease 2019 (COVID-19) can disrupt the gut microbiota balance, and patients usually have intestinal disorders. The intestine is the largest immune organ of the human body, and gut microbes can affect the immune function of the lungs through the gut-lung axis. Many lines of evidence support the role of beneficial bacteria in enhancing human immunity, preventing pathogen colonization, and thereby reducing the incidence and severity of infection. In this article, we review the possible approach of modulating microbiota to help prevent and treat respiratory tract infections, including COVID-19, and discuss the possibility of using probiotics and prebiotics for this purpose. We also discuss the mechanism by which intestinal micro-flora regulate immunity and the effects of probiotics on the intestinal micro-ecological balance. Based on this understanding, we propose the use of probiotics and prebiotics to modulate gut microbiota for the prevention or alleviation of COVID-19 through the gut-lung axis.